SAT0165 Reasons for bdmard cessation and subsequent persistence of second line treatment in a large real world rheumatoid arthritis registry. (12th June 2018) - Youssef, P.; Marcal, B.; Button, P.; Truman, M.; Bird, P.; Griffiths, H.; Roberts, L.; Tymms, K.; Littlejohn, G.
Abstract : Background: The current recommendations for treating Rheumatoid Arthritis (RA) patients (pts) who fail on conventional disease modifying anti-rheumatic drugs (DMARDs) is to use biologic (b) or targeted synthetic (ts) DMARDs. Pts who fail first (1st) line b/tsDMRADs are recommended to go on other b/tsDMARDs; however, reasons for stopping or switching between bDMARDs according to mode of action and the persistence on treatment are not well characterized in real world patient populations. Objectives: The primary objective was to identify the reasons for stopping 1st line b/tsDMARDs in RA pts treated in the clinical practice setting. The secondary objectives were to identify second (2nd) line b/tsDMARDs choices in pts who stop TNF inhibitors (TNFis) within 6 months (mo) due to lack of efficacy and the persistence on these treatments. Methods: Pts ≥18 years with confirmed RA who were treated with 1st line b/tsDMARDs, from 1 August 2010 to 30 June 2017, by physicians participating in the OPAL-QUMI database, were included in the analyses. Reasons for stopping b/tsDMARDs were recorded by the treating physician during routine visits. The following b/tsDMARDs were included abatacept (ABA), adalimumab, certolizumab pegol, etanercept, golimumab, infliximab and tocilizumab (TCZ), rituximab (RTX) and tofacitinib (TFB). Data were analysed using descriptive statistics for continuous variables and frequency counts for categorical variables. Persistence on treatment was summarised using Kaplan-Meier (K-M) methodology. Individual TNFis were combined for simplicity. Results: A total of 6914 pts received 1st line b/tsDMARDs. Median age was 61 years, median disease duration (RA onset to last visit) was 10 years. The majority (75%) were females. Treatment was stopped in 2656 pts (38%); 914 (34%) of these stopped within 6 mo of treatment initiation. The highest and lowest percentage of pts stopping treatment within 6 mo was in pts receiving TFB (54%) and TCZ (17%), respectively (table 1). The most common reasons for stopping therapy within 6 mo were lack of efficacy (45%>ABA, 44%>TNFis, 33%>TFB and 27%>TCZ) and adverse reactions (21%>TFB, 20%>TCZ, 15%>TNFis, 13%>ABA). Stopping due to lack of efficacy-primary failure was highest for TFB (23%). The percentage of pts remaining on 2nd line b/tsDMARD treatment after stopping 1st line TNFis due to lack of efficacy was the highest for TCZ (78%) at 6 mo and RTX (75%) at 12 mo (table 2). Median time to stopping 2nd line treatment was 48 mo (95% CI:17–74) for RTX, 21 mo (95% CI:11–62) for TCZ, 21 mo (95% CI:6–21) for TFB; 11 mo (95% Cl:8–22) for ABA and 9 mo (95% CI:7–12) TNFis. Conclusions: The primary failure rate is lower than previously reported. In pts who failed 1st line TNFis within 6 mo of commencement due to lack of efficacy, 2nd line TNFis resulted in the lowest treatment persistence. These real world data will assist clinicians with treatment choices post primary TNFis failure. Acknowledgements: Sponsored by Roche Products, Pty. Limited. Medical Writing provided by Dr Joseline Ojaimi from Roche. Disclosure of Interest: P. Youssef: None declared, B. Marcal Employee of: Roche Products, Pty. Limited, P. Button Consultant for: Roche Products, Pty. Limited, M. Truman Consultant for: Roche Products, Pty. Limited, P. Bird: None declared, H. Griffiths: None declared, L. Roberts Consultant for: AbbVie, Bristol-Myers Squibb, Janssen, Pfizer, Roche Products, Pty. Limited, UCB, K. Tymms Consultant for: AbbVie, Bristol-Myers Squibb, Janssen, Pfizer, Roche Products, Pty. Limited, UCB, G. Littlejohn Consultant for: AbbVie, Bristol-Myers Squibb, Janssen, Pfizer, Roche Products, Pty. Limited, UCB